HLA-B27 heavy chain homodimers are expressed in HLA-B27 transgenic rodent models of spondyloarthritis and are ligands for paired Ig-like receptors. - Kollnberger, S; Bird, L; Roddis, M; Hacquard-Bouder, C; Kubagawa, H; Bodmer, H; Breban, M; Mcmichael, A; Bowness, P (2004)
HLA-B27 transgenic rats and strains of HLA-B27-transgenic beta(2)-microglobulin (beta(2)m)-deficient mice develop a multisystem inflammatory disease affecting the joints, skin, and bowel with strong similarity to human spondyloarthritis. We show that HLA-B27 transgenic mice and rats express HC10-reactive, beta(2)m-free HLA-B27 homodimers (B27(2)) and multimers, both intracellularly and at the cell surface of leukocytes, including rat dendritic cells. Fluorescent-labeled tetrameric complexes of HLA-B27 homodimers (B27(2) tetramers) bind to populations of lymphocytes, monocytes, and dendritic cells. The murine (and probably rat) paired Ig-like receptors (PIRs) are ligands for B27(2). Thus, B27(2) tetramers stain RBL cells transfected with murine activating PIR-A4 and inhibitory PIR-B receptors. Murine PIR-A and -B can be immunoprecipitated from the RAW264.7 macrophage cell line, and murine PIR-A can be immunoprecipitated from the J774.A1 line using B27(2). B27(2) tetramer staining corresponds to the distribution of PIR expression on lymphoid and myeloid cells and on murine macrophage cell lines. B27(2) can induce TNF-alpha release from the J774.A1 macrophage cell line. The binding of B27(2) to PIR is inhibited by HC10, an mAb that ameliorates arthritis in HLA-B27(+) beta(2)m(-/-) mice. The expression and PIR recognition of B27(2) could explain the pathogenesis of rodent spondyloarthritis.